Protecting Rights and Freedoms : Essays on the Charter's Place in Canada's Political, Legal, and Intellectual life - Russell, John, 1956-; Davis, Steven, 1937-; Bryden, P. (Book collections on Project MUSE., 1994)
In his introduction to this collection of essays by constitutional experts, Philip Bryden says that Canadians can be proud of their commitment to the protection of rights and liberties in the Charter. Canada, he believes, is a better place to live then it would be otherwise. Nevertheless, as the essays in this book reveal, the case in favour of the Charter is not simple or one-sided. For instance, Kim Campbell, minister of justice at the time of writing, and Jeffrey Simpson of the Globe and Mail express concern that the Charter promotes a rights discourse that threatens to overwhelm the ordinary politics of recognizing and accommodating different interests. Dean Lynn Smith of the University of British Columbia law faculty observes that the Charter rights are better understood as complementing than as supplanting traditional mechanisms. The authors, diverse in background and outlook, reflect varying points of view but share a significant degree of consensus on issues that need to be addressed.